Peran Literasi Dalam Penguatan Kompetensi 4C sebagai Keterampilan Abad Ke-21 (Studi Kasus di SMK Al-Khoeriyah Tasikmalaya): Penelitian - Mia Sumiarsih; Ilman Ansori; Yiyih Siti Rodiah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to analyze the role of literacy in strengthening 4C competencies Critical Thinking, Communication, Collaboration, and Creativity as essential 21st-century skills among students at SMK Al Khoeriyah Tasikmalaya. Literacy is understood as a key foundation for vocational graduates to adapt to technological change and workplace demands. Using a qualitative case study approach, the research involved the vice principal of curriculum, vocational subject teachers, and students from grades XI and XII. Data were gathered through observation, structured and semi-structured interviews, and documentation. Data analysis followed Miles, Huberman, and Saldaña’s interactive model, including data reduction, data display, and conclusion drawing, with triangulation used to ensure validity. Findings show that literacy particularly digital and information literacy contributes significantly to the development of critical thinking, creativity, communication, and collaboration through project-based learning activities. However, implementation varies across subjects due to limited teacher readiness, inadequate technological facilities, and assessment systems that do not explicitly evaluate 4C outcomes. The study concludes that literacy can serve as a driver of 21st-century competencies when supported by relevant instructional design and institutional commitment at the school level.